Deployment strategy for static chargers in WRSN - Hao HE; Yong-rui CHEN; Wei-dong YI; Ming LI (Tongxin xuebao)
The traditional deployment strategy of static chargers in wireless rechargeable sensor networks (WRSN) covers all the area.The basic idea is to cover all the positions of nodes.A mathematical model of distance between a charger and the farthest node was established,the relationship between the number of nodes and the mathematical expectation of minimum radius of charging was analyzed,and deployment strategy for static chargers was proposed.The method based on the locations of all nodes that need to be charged in the area,used the smallest enclosing circle (SEC) algorithm and finds the optimal location of the charger through Euclidean delivery boy algorithm.It will decrease charging radius,reduce the minimum required transmitted power,thereby saving the average charging energy consumption.The experimental results demonstrated that the less the number locations that the nodes existed,the more energy will be saved.